Catholic Reformation in Ireland the mission of Rinuccini, 1645-1649 - O hAnnrachain, Tadhg (Oxford University Press, 2002)
In this scholarly and dramatic reappraisal of a central episode in the extension of Catholic reform to Ireland, Tadhg O hAnnrachain situates Rinuccini's mission in its wider European context and provides a perspective on Rinuccini himself.